Crop-wild sunflower hybridization can mediate weediness throughout growth-stress tolerance trade-offs - Presotto, Alejandro Daniel; Hernández, Fernando; Díaz, Marina; Fernández Moroni, Ivana; Pandolfo, Claudio Ezequiel; Basualdo, Jessica; Cuppari, Selva Yanet; Cantamutto, Miguel Angel; Poverene, María Mónica (2018)
Agricultural weeds are plants well-adapted to agricultural environments interfering directly and indirectly with crop production and causing important economic losses worldwide. Crop-wild hybridization is one of the main forces that have ruled weed evolution along with adaptation to agricultural (or benign) environments. Considering the competing demands for resources in any plant, adaptation to agricultural environments might result in an increase in growth but with lower tolerance to stress. In Argentina, most of the non-native H. annuus populations grow on roadsides, ditches, fences, hedgerows (ruderals), but there are also a few cases of H. annuus growing in agricultural field as weeds (agrestals). We asume that weediness of these agrestal biotypes came after crop hybridization as result of growth-stress tolerance trade-offs. Ruderal, agrestal (with evidence of crop introgression), and crop biotypes were contrasted under studies of drought and defoliation stresses, as well as for plant growth under non-stressful conditions and sequences of stress-related genes. The agrestal biotype was less tolerant to defoliation and drought than the ruderal biotype. Drought tolerance variation was largely explained by plant height rate (growth) and defoliation tolerance variation was mainly explained by biomass accumulation (resource allocation). Agrestal biotype sequences of two genes encoding transcription factors involved in stress response, DREB2 and NAC, showed evidence of positive selection in the crop direction. Therefore, selection in the agricultural environment combined with crop hybridization driver the evolution of a well-adapted genetic variant of H. annuus with fast growth but reduced stress tolerance.